What Have We Learned : Macroeconomic Policy after the Crisis - akerlof, george; blanchard, olivier; romer, david (The MIT Press, 2014)
Since 2008, economic policymakers and researchers have occupied a brave new economic world. Previous consensuses have been upended, former assumptions have been cast into doubt, and new approaches have yet to stand the test of time. Policymakers have been forced to improvise and researchers to rethink basic theory. George Akerlof, Nobel Laureate and one of this volume's editors, compares the crisis to a cat stuck in a tree, afraid to move.